The Routledge companion of performance-related concepts in non-European languages
1 online resource.
Keywords: "This volume provides an invaluable research tool and one-of-a-kind reference source for scholars and students worldwide and across the humanities, especially in the fields of theatre, performance, dance, translation and area studies, history (of science) and cultural studies"--